Features of The Audit of Travel Organizations - Eshmamatova Madina (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article discusses the main aspects of audit in the field of tourism, the service sector in general, which in general should be taken into account by the auditor when planning all stages of the audit. At the same time, it is necessary to take into account what role the audited subject plays in tourism: whether he is a uroperator or a travel agent. This determines the specifics of its accounting and reporting system, the selected taxation models, and, accordingly, the auditor's audit operations.